Diuretic Effect of Plasma Dog with Overload Salina - Barrio Tarnawiecki, César Y. (1971)
This paper uses an original experimental model to determine the validity of the hypothesis of humoral natriuretic factor. Small doses of Dog plasma is injected with expansion to other receptors VEC dogs, directly into the left renal artereia. Physiologism of the experimental and contralateral kidney was studied. The results support the hypothesis of that "third factor", they show an apparently independent diuretic and natriuretic action of discrete changes in renal plasma flow and glomerular filtration. The possibility of a reflex nervous mechanism given the contralateral response similar to the experimental kidney arises.